Enhancing student’s conceptual understanding on the patterns of Mendelian genetics through task-based learning - Emmylou Aspacio Borja; Romel Cayao Mutya (University of Muhammadiyah Malang, 2024)
Mendelian genetics are essential for students seeking to comprehend the complexities of inheritance; although fundamental, these biology concepts are difficult for students to understand. This study examined the effectiveness of task-based learning (TBL) in enhancing the students' conceptual understanding of the Patterns of Mendelian Genetics. A pretest and posttest quasi-experimental research design involved an experimental and a control group. An Intrinsic Motivation Inventory questionnaire was utilized to assess the level of intrinsic motivation for task evaluation for the experimental group. Paired t-test was used to compare the pretest and post-test results. Before the intervention, both groups had a low conceptual understanding of the topic. At the end of the intervention, both groups had significantly increased their performances from pretest to posttest scores. The study revealed that TBL is more effective than Traditional Lecture-Based Instruction (TLI), as seen in their enhanced student performance, implying the effectiveness of the TBL as an innovative instructional approach. Participants from the experimental group expressed enjoyment, competence, and ownership of their task activities, and they did not feel nervous and anxious about doing the tasks. Pearson r-correlation was used to establish a relationship among the variables. Perceived choice, pressure/tension, and student performance in the experimental group have low positive correlations, and perceived choice, interest/enjoyment, and performance have a negligible correlation. This approach is highly commendable for biology instruction. By illuminating the effectiveness of active learning in improving student’s conceptual understanding, this study bridges the gap between theoretical-practical gap in genetics via active learning effectiveness.